Slow Growth Storage of Berula erecta in vitro – Effect of Sucrose, Sorbitol and Temperature - Ambrožič-Dolinšek, Jana; Oblonšek, Sanja; Ciringer, Terezija (Agricultura Scientia, 2022)
It has been established that in vitro storage of Berula erecta (Huds.) Coville by slow growth would rationalize the culture maintenance by reducing the number of transfers to fresh medium. Attempts of slow growth were made while maintaining viability by adding sugars and sugar alcohols to the MS medium and lowering the culture temperature in the growthchambers. The effect of low temperatures (13°C and 4°C), different combinations and concentrations of sorbitol (20, 40 g L-1) and sucrose (30, 40 g L-1), and light was tested to determine the viability and ability of B. erecta to recover growth. Increasing sucrose concentration did not inhibit or slow growth. At 23 ± 2°C, the addition of 20 g L-1 sorbitol successfully inhibited growth, while the addition of 40 g L-1 sorbitol resulted in plant senescence after two months of culturing. Storage of B. erecta at 13°C did not effectively inhibit growth and recovery ability in any treatment. The most effective way to maintain B. erecta for long-term slow growth storage in tissue culture while retaining a high level of viability with minimal growth was to culture the plants at 4°C in the dark. This kept the plants viable and capable of regeneration for several months.
Keywords: slow growth storage; Berula erecta; viability; sucrose; sorbitol; temperature